La Europa balcánica : Yugoslavia, desde la segunda guerra mundial hasta nuestros días / Ricardo M. Martín de la Guardia, Guillermo Á. Pérez Sánchez - Pérez Sánchez, Guillermo A.; Martín de la Guardia, Ricardo M. (1964-) (Historia Universal. Contemporánea; 17)
Bibliografía: p. 199-206